2012
DOI: 10.1163/156853712x633956
|View full text |Cite
|
Sign up to set email alerts
|

Immortality of the Soul as an Intuitive Idea: Towards a Psychological Explanation of the Origins of Afterlife Beliefs

Abstract: Abstracthis study tried to investigate if intuitive ideas about the continuation of the Self after death determine the way people represent the state of being dead, and, in this way, investigate possible psychological origins of afterlife beliefs, which constitute a recurrent cultural phenomenon. A semi-structured interview and a self-report questionnaire were used to obtain information on the experience of imagining oneself as dead and the representation of the dead-I of young adults. he results suggest that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
1
6
0
1
Order By: Relevance
“…Participants’ afterlife beliefs were highly varied. Researchers have tended to propose one psychological mechanism or motive to explain belief in an afterlife, including a cognitive predisposition to differentiate material and immaterial states (Bering et al, 2005), the ability to project the continuity of the self in this world beyond death (Pereira et al, 2012), and the use of an “offline social reasoning process” to imagine the continued embodied existence of deceased “loved ones” (Hodge, 2011, pp. 368, 369).…”
Section: Discussionmentioning
confidence: 99%
“…Participants’ afterlife beliefs were highly varied. Researchers have tended to propose one psychological mechanism or motive to explain belief in an afterlife, including a cognitive predisposition to differentiate material and immaterial states (Bering et al, 2005), the ability to project the continuity of the self in this world beyond death (Pereira et al, 2012), and the use of an “offline social reasoning process” to imagine the continued embodied existence of deceased “loved ones” (Hodge, 2011, pp. 368, 369).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies conducted in CSR examining how the fo k anthropomorphizes supernatural agents by representing them with human-like perceptual abilities have proven to be a mixed bag. Whereas participants are recorded re ularly attributing visual and auditory perception to supernatural agents, olfactory, ta ile, and ustatory senses are far less frequently attributed to them (Bek and Lock, 2011;Bering, 2002;Nyhof and Johnson, 2017;Shtulman, 2008;Shtulman and Lindeman, 2016;Watson-Jones et al, 2017) save when the participants are imagining themselves as surviving their own deaths in an afterlife (Pereira et al, 2012). This may, however, be an artifact of how the perceptual questions are asked (Hodge, 2012;Lane et al, 2016).…”
Section: Anthropomorphism Qua Human-like Mindsmentioning
confidence: 99%
“…As I wi l discuss in later section, however, this does not mean that those supernatural beasts are not anthropomorphized. Yet even though intentional agency may not be foremost anthropomorphizing attribute of the supernatural agent,, numerous experimental studies in CSR that have shown that the fo k, beginning in chil hood, both implicitly and explicitly attribute intentional agency to supernatural agents: this includes the afterliving deceased (Astuti and Har is, 2008;Bek and Lock, 2011;Bering, 2002;Gray et al, 2011;Har is and Giménez, 2005;Huang et al, 2013;Pereira et al, 2012;Watson-Jones et al, 2017) and the gods and other supernatural beings (Haslam et al, 2008;Heiphetz et al, 2016;Lane et al, 2010;Ma-Ke lams, 2015;Mori uchi et al, 2018;Shaman et al, 2018;Shtulman, 2008;Shtulman and Lindeman, 2016). But again, attributing intentional agency on its own is not ecifica ly anthropomorphizing the entity.…”
Section: Anthropomorphism Qua Human-like Mindsmentioning
confidence: 99%
“…Experimental studies conducted in CSR examining how the folk anthropomorphizes supernatural agents by representing them with human-like perceptual abilities have proven to be a mixed bag. Whereas participants are recorded regularly attributing visual and auditory perception to supernatural agents, olfactory, tactile, and gustatory senses are far less frequently attributed to them (Bek & Lock, 2011;Bering, 2002;Bering, Blasi, & Bjorklund, 2005;Nyhof & Johnson, 2017;Shtulman, 2008;Shtulman & Lindeman, 2016;Watson-Jones, Busch, Harris, & Legare, 2017) save when the participants are imagining themselves as surviving their own deaths in an afterlife (Pereira, Faísca, & Sá-Saraiva, 2012). This may, however, be an artifact of how the perceptual questions are asked (Hodge, 2012;Lane, Liqi, Evans, & Wellman, 2016).…”
Section: Anthropomorphism Qua Human-like Mindsmentioning
confidence: 99%
“…To date, numerous experimental studies in CSR that have shown that the folk, beginning in childhood, both implicitly and explicitly attribute intentional agency to supernatural agents: this includes the afterliving deceased (Astuti & Harris, 2008;Bek & Lock, 2011;Bering, 2002;Gray, Knickman, & Wegner, 2011;Harris & Giménez, 2005;Huang, Cheng, & Zhu, 2013;Pereira et al, 2012;Watson-Jones et al, 2017) and the gods and other supernatural beings (Haslam, Kashima, Loughnan, Shi, & Suitner, 2008;Heiphetz, Lane, Waytz, & Young, 2016;Lane, Wellman, & Evans, 2010;Ma-Kellams, 2015;Moriguchi, Takahashi, Nakamata, & Todo, 2018;Shaman et al, 2018;Shtulman, 2008;Shtulman & Lindeman, 2016) Another staple of human psychology is our emotions (Damasio, 1994(Damasio, , 1999. Like intentional agency, emotional states are frequently anthropomorphized onto things-real or imaginary-in our environment to aid in our understanding and predicting of that things perceived behavior.…”
Section: Anthropomorphism Qua Human-like Mindsmentioning
confidence: 99%